2013
DOI: 10.1111/jocn.12174
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue self‐management: a survey of Chinese cancer patients undergoing chemotherapy

Abstract: Findings highlight the need for nurses to explore patients' use of fatigue self-management behaviours and the effectiveness of these behaviours in reducing fatigue. Interventions that improve patients' self-efficacy and neighbourhood supports have the potential to improve outcomes from fatigue self-management behaviours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 45 publications
2
19
0
1
Order By: Relevance
“…A variety of behaviors was implemented with very low to moderate self-efficacy, and most of these behaviors were rated as providing low to moderate relief. Consistent with the findings from previous literature, 11,14 the current Chinese sample reported taking prescribed medication as one of the most frequent and useful NVSM behaviors, thus emphasizing medication adherence as a significant component of effective NVSM.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A variety of behaviors was implemented with very low to moderate self-efficacy, and most of these behaviors were rated as providing low to moderate relief. Consistent with the findings from previous literature, 11,14 the current Chinese sample reported taking prescribed medication as one of the most frequent and useful NVSM behaviors, thus emphasizing medication adherence as a significant component of effective NVSM.…”
Section: Discussionsupporting
confidence: 91%
“…Findings relating to the SM of fatigue are reported in a manuscript accepted for publication in the Journal of Clinical Nursing. 11 The present article reports the data related to Chinese cancer patients' use of SM behaviors relating to CINV and considers various health, individual, and environmental factors that might be associated with use of such behaviors. n Literature Review Early Western studies of CINV SM behaviors involving small samples (N G 40) reported that patients most frequently took prescribed antinausea medication and rested in a quiet place to manage their nausea, with these strategies achieving more relief than other less commonly reported strategies, such as modifying food intake.…”
mentioning
confidence: 99%
“…Thus, supporting self‐efficacy in performing self‐care behaviours could facilitate coping with the bothersome symptoms of chemotherapy and cancer, such as fatigue. A study reported that cancer patients’ self‐management behaviours to cope with fatigue were moderately sufficient, and social support positively influenced the cancer patients’ self‐management behaviours (Lou et al., ). This study also found that greater self‐efficacy scores were associated with more effective relief, and the outcomes of self‐management behaviours to cope with fatigue were better in these patients with cancer (Lou et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Nurses may help patients develop positive attitudes towards performing tasks, such as providing positive feedback and encouragement, distracting the patients from negative thoughts or memories and assisting the patients with daily life activities. These interventions may contribute to mediating cancer-related stress, managing the detrimental effects of fatigue and improving emotional and social well-being as well as QoL Kim et al, 2017;Lev & Owen, 2000;Lev et al, 2001;Lou, Yates, McCarthy, & Wang, 2013). Williams et al, 2016) .…”
Section: Relationship Between Qol Scores and Level Of Fatiguementioning
confidence: 99%
“…반면에 정서적 지지가 없을 경우 암환자의 자기효능감은 낮아진다고 지적한다 (11). 특히 항암화학요법을 받는 암환자에게 있어 자기효능감은 자가관리의 예측요인임을 보고하고 있다 (12 질에서는 치료현황에 따른 유의한 차이가 없었다. …”
unclassified